High performance rechargeable aluminium ion batteries enabled by full utilization and understanding of polyaniline cathodes - Wei, Guokang; Qiao, Jia; Li, Xin; Tao, Fei; Xue, Weixi; Hu, Sijiang; Luo, Zhenhua; Yang, Jianhong (Elsevier, 2024)
As a renowned conductive polymer, polyaniline (PANI) shows remarkable potential in organic cathode materials for rechargeable aluminium ion batteries (RAIBs). However, existing research has not given sufficient understanding and explanation of the structure and states of PANI but failed to achieve ideal electrochemical performance. In this study, we differentiate and investigate for the first time its primary-doped (PANI-1), re-doped (PANI-Re), secondary-doped (PANI-2), and emeraldine based (PANI-EB) forms, meanwhile attempt to enhance the conductivity of PANI-EB using multi-walled carbon nanotubes (PANI-EB@C). Among them, the high-doped PANI-2 and non-doped PANI-EB exhibit theoretical capacity utilization far superior to lower doped PANI-1 and PANI-Re, with both specific capacities reaching approximately 225 mAh/g (full capacity utilization rate of 76.53 %) at a current density of 1 A/g, while maintaining capacity retention rates of 92.89 % after 2000 cycles and 92.44 % after 5000 cycles, respectively. Furthermore, the high-conductivity PANI-EB@C displays a discharge specific capacity of 284 mAh/g (full capacity utilization rate of 96.59 %), with a capacity retention rate of 91.19 % after 5000 cycles. Electrochemical analysis, Gaussian theoretical calculations, ex-situ characterization collectively indicate that the electrochemical performance of doped PANI is positively correlated with the degree of doping-induced conductivity changes, while the unique internal redox process of PANI-EB enhances the release of performance and could be further optimized by the assistant of conductivity medium. This work advances the classification of the electrochemical performance and structural understanding of PANI cathode materials to an extremely high stage, towards the practical application of a low-cost, high-performance, sustainable, and green cathode material in large-scale energy storage devices.
Keywords: Rechargeable aluminium ion batteries; Organic cathode; Polyaniline; Doping; Emeraldine base